Situs Kota Rebah Di Tanjung Pinang, Kepulauan Riau: Pertapakan Istana Atau Bangunan Lain - Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2015)
An excavation at the site of Kota Rebah (also known as Kota Lama) in the city of Tanjung Pinang, Kepulauan Riau (Riau Islands) Province in October 2014, which was carried out by the Cultural Office of Kepulauan Riau Province, in cooperation with the Medan Archaeological Centre and the Cultural Heritage Conservation Office of Batusangkar, is an attempt to explore remains of the cultural history of Kepulauan Riau community, including to understand about their types and functions. This is in relation to the site and remains of a building that is believed by some local inhabitants to be a site and remains of the palace of the Melayu kings in the past. The data collected using survey and excavation method indicate that the site and building remains are more likely to be remains of a loji (fort with warehouses) than the site and remains of a palace.